2017
DOI: 10.35799/jis.17.2.2017.17279
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Uji Mikrobiologi Dan Logam Berat Pada Scrub Berbahan Dasar Kapur Sirih

Abstract: ANALISIS UJI MIKROBIOLOGI DAN LOGAM BERAT PADA SCRUB BERBAHAN DASAR KAPUR SIRIHABSTRAKKapur sirih dibuat dari pengolahan batu kapur hasil pembakaran yang direndam dalam air dalam waktu satu sampai dua minggu sampai hancur dan berbentuk seperti pasta. Kapur sirih ini pada zaman dahulu digunakan oleh para orang tua sebgai campuran ramuan untuk merawat gigi.sedangkan pada pengobatan-pengobatan tradisional juga digunakan sebagai obat mengatasi gusi bengkak,bisul,masalah haid serta penyakit kulit seperti menghilang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Larsen et al used Mg 2+ to Ca 2+ ratio of 1:1000 or deficit amount of CaCl 2 with respect to urea to provide larger crystal size 11 . This was further validated by a study by Apriliani et al where Mg 2+ ions lead to decreased rate of carbonate precipitation and modified morphology and structure 12 . Also, Boyd et al observed transition from angular to spherical precipitates with an addition of Mg 2+ ions 13 .…”
Section: Introductionmentioning
confidence: 53%
“…Larsen et al used Mg 2+ to Ca 2+ ratio of 1:1000 or deficit amount of CaCl 2 with respect to urea to provide larger crystal size 11 . This was further validated by a study by Apriliani et al where Mg 2+ ions lead to decreased rate of carbonate precipitation and modified morphology and structure 12 . Also, Boyd et al observed transition from angular to spherical precipitates with an addition of Mg 2+ ions 13 .…”
Section: Introductionmentioning
confidence: 53%
“…This occurs to acrylic emulsion paint samples that have a pH level of 7. The best research results were samples of acrylic emulsion paint at 27 °C and 50 °C at pH 9 with no smell and no lumps (Table 1 TPC can be used as an indicator of product hygiene, environmental microbial analysis of the finished products, and process control indicators, and can be used as a basis for suspicions that a product is acceptable or not based on its microbiological quality [7].…”
Section: Resultsmentioning
confidence: 99%
“…It is because if the pH of a product is too high or low, it will irritate the skin. Apriliani and Aniriani (2017) explains that skin products should have a pH of around 5.5, while according to SNI Number 16-4399-1996, the recommended pH for cream products ranges from 4.5-8.0.…”
Section: Ph Similarity Testmentioning
confidence: 99%